Numerical Simulation of Threat-Independent Progressive Collapse - Elvira E.; Mendis P.; Whittaker A. (Civil Engineering Dimension, 2011)
A threat-independent approach is usually utilized for progressive collapse analysis of buildings. This approach is referenced in the current guidelines such as “Progressive Collapse Analysis and Design Guidelines for New Federal Office Buildings and Major Modernization Projects” by the U.S. General Service Administration and “Design of Buildings to Resist Progressive Collapse” by the U.S. Department of Defence. However, more studies are required to accurately observe the influence of structural parameters to the response of structures in progressive collapse phenomenon. A parametric study was conducted using advanced nonlinear finite element analysis to assess the utility of the procedures in these documents. The results of the numerical simulations show that a variation of the beam dimensions moderately affects the dynamic load factor. The load factor increases as the beam dimensions increase. Other parameters such as the column dimensions, number of storeys and span lengths, have only negligible effects on the value of the dynamic load factor.